A Complete Axiomatization of Simulation for Regular CCS Expressions - Frendrup, Ulrik; Jensen, Jesper Nyholm (BRICS Report Series, 2001)
This paper gives axiomatizations of strong and weak simulation over regular CCS expressions. The proof of completeness of the axiomatization of strong simulation is inspired by Milner’s proof of completeness of his axiomatization for strong equivalence over regular CCS expressions. Soundness and completeness of the axiomatization for weak simulation is easily deduced from the corresponding result for the axiomatization of strong simulation over regular CCS expressions.